Arbeitsmarktpolitik in der Europäischen Währungsunion - Norbert Berthold; Rainer Fehn (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, Wirtschaftsordnung und Sozialpolitik, 2000)
While policymakers in Europe were busy implementing EMU during the past decade, persistently high unemployment, which should have been the main policy issue from a normative point of view, was essentially left untackled in most continental European countries. This poses the urgent question which approach labor market policy should take now in fighting unemployment and which changes have come about with EMU. To deal with this question, the paper proceeds in three steps. It is first shown that a web of institutions on labor, goods and capital markets, which are distinctly different from Anglo-Saxon countries and which are interconnected by politico-economic forces, is to blame for the dismal situation on most continental European labor markets. It is second argued that EMU is not likely to boost automatically employment growth. It is third outlined which policy measures are key to alleviate unemployment in continental Europe and it is discussed whether EMU makes the actual implementation of these measures more likely.
Keywords: 330; Arbeitsmarktpolitik; Europäische Wirtschafts- und Währungsunion; Public Choice; Strukturelle Arbeitslosigkeit; Arbeitsmarktflexibilisierung; EU-Staaten